2003
DOI: 10.1093/rheumatology/keg079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rheumatoid arthritis on sexual activity and relationships

Abstract: RA impacts on the sexual lives of a large minority of patients and this is a problem that patients and health professionals are reluctant to discuss face to face. However, patients do appear to be willing to complete questionnaires and this may be an acceptable format for assessment. Further training and support is needed by nurses and other health professionals in this sadly neglected area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
5
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 7 publications
7
159
5
22
Order By: Relevance
“…For example, patients may be reluctant or too embarrassed to broach personal topics with an HCP. A similar issue has been reported for RA, where only 39% of patients who answered a questionnaire relating to personal relationships felt comfortable discussing such topics with an HCP [77]. Furthermore, a patient's trepidation to disclose information regarding their wellbeing may prevent them from asking for further psychological help.…”
Section: Improving Communication Between Patients and Physiciansmentioning
confidence: 61%
“…For example, patients may be reluctant or too embarrassed to broach personal topics with an HCP. A similar issue has been reported for RA, where only 39% of patients who answered a questionnaire relating to personal relationships felt comfortable discussing such topics with an HCP [77]. Furthermore, a patient's trepidation to disclose information regarding their wellbeing may prevent them from asking for further psychological help.…”
Section: Improving Communication Between Patients and Physiciansmentioning
confidence: 61%
“…Another explanation for a better marriage satisfaction in chronic diseases might be the positive support of spouses. 32,33 Similarly, the majority of our patient group explained that RA had a mild or no effect on their marriage. In a study by Hill et al, 32 65% of the patients reported that RA did not affect their marriage.…”
Section: Discussionmentioning
confidence: 64%
“…32,33 Similarly, the majority of our patient group explained that RA had a mild or no effect on their marriage. In a study by Hill et al, 32 65% of the patients reported that RA did not affect their marriage. In another study investigating RA, marriage and pain by Waltz et al, 33 negative attitudes from spouses such as criticizing were associated with worsening of the complaints, particularly pain.…”
Section: Discussionmentioning
confidence: 64%
“…Psychological responses to chronic illness can include feelings of loss of independence, disrupted self-image, depression and anxiety (Basson and Schultz 2007). The physical components can include pain, fatigue, reduced functional ability, reduced strength and mobility (Hill, Bird, and Thorpe 2003). Both the psychological and the physical factors interrupt and affect sexual health in several ways.…”
Section: How Does Ra Affect Sexual Health and Intimate Relationships?mentioning
confidence: 99%
“…The impact of a chronic disease on sexual health can be due to indirect factors influencing sexual function such as altering self-image, fatigue, pain and dependency (Basson and Schultz 2007). Sexual health is one of the domains that can be professionals (Abdel-Nasser and Ali 2006;Akkas 2010;Josefsson and Gard 2010;Hill, Bird, and Thorpe 2003;Rkain et al 2006). Possible reasons for this will be discussed further in this chapter.…”
Section: Introductionmentioning
confidence: 99%